Cover crops effects on anisotropy of unsaturated soil hydraulic properties - Polich, Nicolás Guillermo (2022)
No tillage (NT) is frequently implemented in simplified agricultural systems, which has negative effects on soil physical quality. Among the suggested practices to preserve the physical fertility of soils under NT are winter cover crops (CC). Soil physical degradation affects the soil pore configuration and therefore it can generate a change in the directionality of the properties that depend on it. The objective of this study was to determine the effect of cover crop incorporation under NT on the soil pore system configuration and on the anisotropy of the unsaturated hydraulic properties in a Typic Argiudoll. The results showed that the inclusion of cover crops modifies the soil pore configuration increasing the structure porosity. The inclusion of CC modifies the anisotropy of unsaturated hydraulic conductivity in the medium saturation region. The pore size distribution behaves as isotropic as expected for a scalar variable.